Change Management and Value-Based Healthcare Implementation: The Mediating Role of Employee Engagement in Healthcare of Saudi Arabia - Aljohani, Rayhanah Sulaiman; Abdulsamad, Akram (Advances in Social Sciences Research Journal, 2026)
The global transition toward Value-Based Healthcare (VBHC) has intensified the need to understand how healthcare organizations translate reform strategies into sustained clinical practice. While existing research has largely emphasized structural and policy dimensions of VBHC, limited attention has been given to the organizational and behavioral mechanisms supporting implementation. This study develops a conceptual framework explaining how change management practices influence VBHC implementation effectiveness through employee engagement within the context of Saudi Arabia's healthcare transformation. This paper adopts a conceptual research design grounded in social exchange theory and the job demands-resources model. By synthesizing literature from organizational change, employee engagement, and healthcare implementation research, the study proposes an integrated framework linking change management practices, employee engagement, and VBHC implementation effectiveness in the Madinah Health Cluster. The proposed framework conceptualizes employee engagement as a central mediating mechanism through which supportive change management practices translate organizational reform initiatives into sustained implementation behaviors. Change management functions both as a relational signal of organizational support and as a resource enabling healthcare professionals to manage transformation-related demands. The study advances healthcare management scholarship by integrating relational and motivational theories to explain VBHC implementation as a behavioral and organizational process rather than solely a structural reform. The framework highlights the importance of people-centered change strategies for achieving sustainable healthcare transformation under Saudi Arabia's Vision 2030. By offering a theory-driven model grounded in a non-Western healthcare context, this study provides a novel behavioral perspective on VBHC implementation and contributes to emerging research on cluster-based healthcare reform.